The use of Facebook by local authorities: a comparative analysis of the USA, UK and Spain. (2018) - Miranda, F. Javier; Chamorro, Antonio; Rubio, Sergio
The social networks have increased the ways in which public administrations can actively interact with the public. However, these new means of communication are not always used efficiently to create an open and two-way relationship. The purpose of this study is to analyse the presence on and use of the social network Facebook by the large councils in the USA, UK and Spain. This research adapts Facebook assessment index (FAI) to the field of local authorities. This index assesses three dimensions: popularity, content and interactivity. The results show that there is no relationship between the population of the municipality and the degree of use of Facebook by the council, but there are notable differences depending on the country. By creating this ranking, we are helping those responsible for this management to carry out benchmarking activities in order to improve their communication strategy on the social networks.